Interview of Flora Tibazarwa Director at Commission for Science and Technology (COSTECH), Tanzania - Tibazarwa, F.I. (International Livestock Research Institute, 2014)
Interviews of selected participants; views from the Regional Experts Workshop on Industrial Effluents Management in East Africa held on 19-20 May 2014, Ethiopia